MENGENAL TEORI DEMOKRASI DAN TEORI KEWENANGAN DALAM ILMU HUKUM - Danel Aditia Situngkir (Ensiklopedia of Journal, 2023)
Democracy is a form or mechanism of a country's government system as an effort to realize people's sovereignty (the power of citizens) over the country to be run by the government of that country. While authority comes from the basic word authority which is interpreted as a matter of authority, rights and powers possessed to do something. Authority is what is called formal power, power that comes from legislative power or from executive-administrative power. Authority which usually consists of several authorities is power over a certain group of people or power over a field of government. Democracy and Authority must be based on existing legal provisions (constitution), so that this authority is a legitimate authority. Thus officials (organs) in issuing decisions are supported by this source of authority. Stroink explained that sources of authority can be obtained for government officials or organs (institutions) by way of attribution, delegation and mandates. The authority of government organs (institutions) is an authority strengthened by positive law to regulate and maintain it. Without authority, a correct juridical decision cannot be issued and in accordance with democratic principles. Regarding the nature of governmental authority, namely that it is bound, optional, and free, especially in relation to the authority to make and issue decisions (besluiten) and decrees (beschikkingan) by government organs, so that decisions are known to be bound and free.